1998
DOI: 10.1002/(sici)1096-9063(199809)54:1<43::aid-ps778>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of the herbicide dinitro-o-cresol on mitochondrial bioenergetics

Abstract: The herbicide dinitro‐o‐cresol (DNOC) was evaluated for its effects on bioenergetic activities of potato tuber mitochondria to elucidate its mechanism of action and to compare its toxicological properties with those of the chemically related uncoupler dinitrophenol (DNP). DNOC acts as a typical uncoupler, similarly to the classical uncouplers DNP and carbonylcyanide p‐trifluoromethoxyphenyl‐hydrazone (FCCP). Low concentrations of DNOC (<100 μM) maximally stimulate succinate‐supported respiration of plant mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It was explained that in their electron microscopic investigations, swelling of mitochondria and breaking up of the mitochondrial cristae of hepatocytes in diazinon-treated groups were observed. In another study, Vicente et al (1998) showed that liver mitochondria of rats are much more sensitive than the mitochondria of plants. All these studies show that DNOC affects enzyme activityes.…”
Section: Resultsmentioning
confidence: 99%
“…It was explained that in their electron microscopic investigations, swelling of mitochondria and breaking up of the mitochondrial cristae of hepatocytes in diazinon-treated groups were observed. In another study, Vicente et al (1998) showed that liver mitochondria of rats are much more sensitive than the mitochondria of plants. All these studies show that DNOC affects enzyme activityes.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, DNOC mimics the physiological effects of decouplers by stimulating the respiration of animal and higher plant mitochondria (Vicente et al 1998). Because of this mechanism, inhibitory effects on Y(II) as well as on growth of exposed M. aquaticum whorls were expected as subsequent effects.…”
Section: Positive Control For the Invasive And Non-invasive Observatimentioning
confidence: 99%
“…DNOC toxicity may result from the uncoupling effect on mitochondrial oxidative phosphorylation as previuously proposed (Castilho et al, 1997;Vicente et al, 1998), and was evaluated by comparing its influence at different concentrations in soybean cell culture growth.…”
Section: Concentration-dependent Cell Death Induced By Dnoc In Soybeamentioning
confidence: 99%
“…Previous studies using isolated mitochondria have indicated that DNOC mimics the physiological effects of uncouplers by dissipating the transmembrane electrical potential (Dc) and stimulating respiration (Vicente et al, 1998). Accordingly, DNOC at low concentrations would act as a typical uncoupler; but higher concentrations of DNOC would simultaneously uncouple and inhibit respiration.…”
Section: Article In Pressmentioning
confidence: 99%